Comparison of Lexical Density and Grammatical Intricacy in News Text of Readability - Meryta Sri Rahayu; Aceng Ruhendi Syaifullah (Universitas Sebelas Maret, 2022)
This study aims to determine the density of a news text published by the Business of Fashion and the New York Times as well as the legibility of the news text in helping readers understand. Based on this qualitative study, it was found that from both types of texts with the same theme, the results of the lexical density and Grammatical Intricacy of the two texts were obtained with the following results. T1 has a lexical density index of 58.13% with a Grammatical Intricacy level of 12 and T2 has a lexical density index of 54.18% with a Grammatical Intricacy level of 8. It can be concluded that the reader will more easily understand T2 than T1 because of the results of the index calculation from lexical density and Grammatical Intricacy owned by the two texts.